European Commission publication RP-162 as a strong reference for reducing patient radiation dose: Results from an angiography equipment updating. (March 2020) - Taddeucci, A.; Piffer, S.; Redapi, L.
Highlights: RP 162 report establishes new suspension levels for fluorographic acquisition. The application of RP 162 can help to obtain radiological equipment update. New image processing algorithms can lead to an important patient dose reduction in interventional procedures.